Effect of Ramadan fasting on fatigue, mood, sleepiness, and health-related quality of life of healthy young men in summer time in Germany: A prospective controlled study. (1st April 2017) - Nugraha, Boya; Ghashang, Samaneh Khoshandam; Hamdan, Imad; Gutenbrunner, Christoph
Abstract: Muslims around the world fast during the lunar month of Ramadan. The month consists of 29 or 30 days, which vary in length depending on geographic location and the time of year. During this month, Muslims abstain from food, drink, smoking, and sex from dawn until sunset. In 2015, Ramadan fell during the summer. As a result, Muslims in Germany fasted 19 h a day. Previous research has shown associations between fasting and mood enhancement. This study aimed to determine the effect of fasting on young, healthy males who fasted in Germany during Ramadan 2015. In particular, this study examined the impact of fasting on mood, fatigue, and health-related Quality of Life (QoL). This study had 2 groups: fasting group (FG; n = 25), and non-fasting group (NFG; n = 25). In FG, participants were assessed at four different points: one week before Ramadan (T1), mid Ramadan (T2), the last days of Ramadan (T3), and one week after Ramadan (T4). In NFG, participants were assessed only at T1 and T3. The results revealed that there were no significant differences between the participants in the FG and the NFG at T1 or T3 for any of the outcomes. However, participants in the FG demonstrated significant improvement from T2 to T4 in fatigue (visual analogue scale p < 0.01; fatigue severity scale:p < 0.01), mood (Beck's Depression Index-II; ANOVA; p < 0.05), and sleepiness during day time (Epworth Sleepiness Scale: ANOVA; p < 0.01). Participants in the FG also experienced significant loss of body weight (ANOVA; p < 0.001), body mass index (ANOVA; p < 0.001), skeletal muscle mass (ANOVA; p < 0.01) and fat free mass (ANOVA; p < 0.01). Findings demonstrate that Ramadan fasting did not significantly influence mood, fatigue and QoL, when compared to NFG. Even, it gives benefit to fasting group with regard to these parameters.